Nueva correlación generalizada para estimar la presión de vapor - Cardona-Palacio, Luis Fernando (Revista Científica, 2016)
In this work, a new generalized correlation for pure substances is proposed for the estimation of vapor pressure, applicable in wide temperature range. Was used equilibrium liquid-vapor data with 28 refrigerants and minimizing the sum of the squares of the relative deviation in liquid-vapour pressure were determined the parameters and constants characteristics of the new equation and generalized for any pure substance using the acentric factor. Vapor pressure predictions were made for 45 pure substances who they didn´t not participate in the minimization, generated percent relative average deviation of 1.6073%. The results were compared with others equations for calculating the vapor pressure and the comparison indicates that the proposed method provide more accurate results than other methods used in this work. Finally, the calculations of enthalpies of vaporization were done with deviations of 0.880% and the Waring criterion was applied to check the constants presed in this paper